2009
DOI: 10.1002/ps.1765
|View full text |Cite
|
Sign up to set email alerts
|

Rapid method for detecting resistance to a QoI fungicide in Plasmopara viticola populations

Abstract: It is proposed that the nested PCR-RFLP method is a high-speed, sensitive and reliable tool for detecting azoxystrobin-resistant P. viticola populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Although a biological test (Wong and Wilcox 2000;Genet et al 1997) or molecular tools have been used to quantify the resistance alleles using real-time q-PCR, ARMS PCR or PCR, (Collina et al 2005;Grasso et al 2006;Toffolatti et al 2007;Sirven and Beffa 2003) or to detect resistant haplotypes using the CAPS method, (Corio-Costet et al 2006;Baudoin et al 2008;Furuya et al 2009) little is known about the fitness of QoIresistant isolates. One study suggested that an artificial P. viticola population containing 5% of resistant isolates tended to increase QoI sensitivity (Genet et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although a biological test (Wong and Wilcox 2000;Genet et al 1997) or molecular tools have been used to quantify the resistance alleles using real-time q-PCR, ARMS PCR or PCR, (Collina et al 2005;Grasso et al 2006;Toffolatti et al 2007;Sirven and Beffa 2003) or to detect resistant haplotypes using the CAPS method, (Corio-Costet et al 2006;Baudoin et al 2008;Furuya et al 2009) little is known about the fitness of QoIresistant isolates. One study suggested that an artificial P. viticola population containing 5% of resistant isolates tended to increase QoI sensitivity (Genet et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…QoI fungicides are highly selective and site‐specific fungicides that inhibit mitochondrial respiration by binding to the ubiquinol‐oxidising pocket, called the Qo site, of the cytochrome bc 1 enzyme complex . A single amino acid substitution at residue 143 (G143A) of cytochrome b of some plant pathogens confers resistance to QoI fungicides . The G143A mutation has been reported in B. cinerea.…”
Section: Introductionmentioning
confidence: 99%
“…In Japanese vineyards, azoxystrobin, a QoI fungicide, is frequently applied to prevent grape downy mildew caused by Plasmopara viticola . However, the resistance of certain P. viticola populations to azoxystrobin emerged in 2008 and is spreading throughout Japan . Under these circumstances, QoI‐fungicide‐resistant B. cinerea from Japanese vineyards was isolated.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, although fenhexamid was registered in 2000, it is not widely used and thus, the existence of fenhexamid resistance in B. cinerea has not been reported in Japan. Molecular-based techniques have been developed to rapidly detect the sensitivity of fungi to several fungicides by taking advantage of point mutations in target genes (Oshima et al 2002;Paplomatas et al 2004;Banno et al 2008, Furuya et al 2009Saito et al 2009). A rapid method for the detection of fungicide resistance is necessary for viticulturists to better understand the incidence of resistance in B. cinerea populations in their vineyards.…”
Section: Introductionmentioning
confidence: 99%